Meningkatkan Kesadaran Masyarakat Akan Pentingnya Menjaga Kebersihan Lingkungan - Hasaya, Haudi; Nuraliyah, Andi; Spalanzani, Widya; Hastowo, Muhammad Agung; Ramadhan, Faizal; Naufaldi, Zulfikri; Timotius, Unggul; Pratama, Andhika Rifqy; Prasetyo, Muhammad Rehan; Hakim, Fathurrahman; Zaki, Abrori; Fahrizi, Irzal; Putri, Dyah Ardhana Mahda (Jurnal Sains Teknologi dalam Pemberdayaan Masyarakat, 2025)
In Indonesia, including at the Faculty of Engineering, the higher education curriculum integrates Real Work Lecture Activities (KKN). KKN aims to improve students' ability to solve community problems using science and technology. This article discusses the implementation of KKN at the Faculty of Engineering (2025),, with special emphasis on the role of students in environmental management, community welfare, and local infrastructure development. Through involvement in construction, design, and infrastructure maintenance projects, students learn to collaborate with communities, improve their technical abilities, and understand how engineering projects have a social impact. Students' social awareness and responsibility as prospective engineers are also increased through the application of problem-based learning and community service. The results of KKN at the Faculty of Engineering really help academic development and sustainable development and quality of life.